Human amniotic membrane conditioned medium inhibits proliferation and modulates related microRNAs expression in hepatocarcinoma cells - Riedel, Rodrigo Nicolas (2019)
The placental stem cells have called the focus of attention for their therapeutic potential to treat different diseases, including cancer. There is plenty evidence about the antiproliferative, antiangiogenic and proapoptotic properties of the amniotic membrane. Liver cancer is the fifth cause of cancer in the world, with a poor prognosis and survival. Alternative treatments to radio- or chemotherapy have been searched. In this work we aimed to study the antiproliferative properties of the human amniotic membrane conditioned medium (AM-CM) in hepatocarcinoma cells. In addition, we have analyzed the regulation of pro and antiOncomiRs expression involved in hepatocarcinoma physiology. We have determined by 3H-thymidine incorporation assay that AM-CM inhibits DNA synthesis in HepG2 cells after 72 h of treatment. AM-CM pure or diluted at 50% and 25% also diminished HepG2 and HuH-7 cells viability and cell number. Furthermore, AM-CM induced cell cycle arrest in G2/M. When proliferation mechanisms were analyzed we found that AM-CM reduced the expression of both Cyclin D1 mRNA and protein. Nuclear expression of Ki-67 was also reduced. We observed that this CM was able to promote the expression of p53 and p21 mRNA and proteins, leading to cell growth arrest. Moreover, AM-CM induced an increase in nuclear p21 localization, observed by immunofluorescence. As p53 levels were increased, Mdm-2 expression was downregulated. Interestingly, HepG2 and HuH-7 cells treatment with AM-CM during 24 and 72 h produced an upregulation of antiOncomiRs 15a and 210, and a downregulation of proOncomiRs 206 and 145. We provide new evidence about the promising novel applications of human amniotic membrane in liver cancer.